Subtitling Without Context: How Does the Lack of Pictures and Sounds Affect the Translation of an Audiovisual Text? - Ahonen, Tuuli (Journal of Audiovisual Translation, 2024)
In this article, subtitling without context refers to situations in which subtitlers do not have access to the image and sound of an audiovisual text, which they need to carry out their translation processes efficiently and successfully. Audiovisual texts, such as movies, need to be seen and heard to be understood and their meaning translated. What happens if the video material is not available or incomplete? This is the question that this study strives to answer. The key concepts discussed in this article are the multimodality of audiovisual texts, context, relevance, and cognitive load. An empirical subtitling test was conducted with translation students at a Finnish university to examine these concepts and their impact on translation processes and products. Two sets of translations were analyzed with a multilayered contrastive analysis. In addition, the participants wrote short translation diaries that were analyzed using content analysis. The students’ translation diaries indicated that it is impossible to time subtitles, make line breaks, and understand references to places and characters, to name but a few difficulties reported by the participants in the test. In addition, the analysis of the diary entries revealed that translating without context reportedly increased the participants’ cognitive load, which in turn made translation processes less efficient and more time-consuming. Lay Summary Movies, television series and videogames can be called audiovisual texts as they convey their meaning with sounds and images. The translators of such texts are called subtitlers and the end products of their translation processes, subtitles. In this article, subtitling without a context refers to situations in which the subtitler does not have access to the image and sounds of an audiovisual text. Audiovisual texts need to be seen and heard to be wholly understood as well as translated efficiently and successfully. What happens if the video material is no available or it is not ready? This is the questions we wish to answer. The key concepts discussed in this article are the multimodality of audiovisual texts, context, relevance, and cognitive load. Multimodality means that audiovisual texts use different ways, such as pictures, texts, music and speech to tell the stories. Context refers to the situation in which language is used and translated. Relevance theory weighs what are the most important things needed to be told with minimal costs, costs in this case being the number of characters in the subtitles. Cognitive load on the other hand refers to the psychological processes and memory use that are ongoing in translation processes. We made a translation test with students from a Finnish university. They translated a written dialog list without seeing the video material it was from. Then they translated it again, but this time with the video. Then these translations were compared with each other as well as with the video’s images and sounds. This method of comparison in this article is called multilayered contrastive analysis. The students also wrote short translation diaries about their experiences. They reported that timing and doing line breaks were impossible without the video. Timing refers to the process of making the subtitle lines appear at the same time as the characters are speaking and line breaks refer to the division of sentences and words in the subtitle lines. The participants wrote to their translation diaries that it was difficult to translate without the video. It was mentally tiresome and because of this, it took much time to finish the translations. The students also were afraid that they made many mistakes, and they used a lot of time second guessing their solutions.